Existence and Uniqueness Solutions of a BVP for Nonlinear Caputo-Hadamard Fractional Differential Equation - Boutiara, Abdelatif; Benbachir, Maamar; Guerbati, Kaddour (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we study the existence and uniqueness of solutions for a nonlinear fractional boundary value problem with Caputo-Hadamard derivative. New existence and uniqueness results are established using Banach contraction principle. Other existence results are obtained using scheafer’s and krasnoselskii’s fixed point theorems. At the end, some illustrative examples are presented.